The nutritional impact of diversified cropping systems: comparing diversified cropping patterns in Rangpur, Bangladesh - Md. Arifur Rahaman; Alanuzzaman Kurishi, A.S.M.; Cheesman, Stephanie; Hossain, Md. Khaled; Parupalli, V.L. Bharathi; Md. Afzal Hossain; Hossain, Shakhawat; Ferdous, Zannatul; Huda, Md. Shamsul; Gathala, Mahesh Kumar; Krupnik, Timothy J. (TAFSSA, 2024)
Bangladesh relies heavily on rice-based cropping systems to ensure food security. However, this dependence limits crop diversification, which is vital for improving agricultural productivity in a densely populated country with limited arable land. This trial summarizes the nutritional yield results from diversified cropping systems after one complete cycle. The study area was selected based on factors such as food security, nutrition adequacy, environmental degradation, and climate challenges—key considerations for achieving TAFSSA’s goals. The research aims to promote crop diversification and identify strategies for cultivating nutrient-rich crops that provide essential macro- and micronutrients.